2016
DOI: 10.1097/sla.0000000000001564
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work and Functional Outcomes After Major Trauma

Abstract: Improvement in outcomes over the study period was observed, although ongoing disability was common at 24 months. Recovery trajectories differed by patient characteristics, providing valuable information for informing prognostication and service planning, and improving our understanding of the burden of nonfatal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
154
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 42 publications
13
154
5
1
Order By: Relevance
“…There were some common findings with other studies, such as poorer outcomes with increasing age,13 42 and in those with pre-existing conditions 7 13…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…There were some common findings with other studies, such as poorer outcomes with increasing age,13 42 and in those with pre-existing conditions 7 13…”
Section: Discussionsupporting
confidence: 67%
“…Recent research by Gabbe et al reported declining function over time following major trauma in older age groups, people with significant pre-existing conditions, low fall injuries and isolated head injuries 13. All of these factors are particularly relevant to older people and although they were not specifically identified in this review, this is more likely a reflection of the lack of literature rather than inconsistencies between studies.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Care at MTS has been shown to improve functional outcomes (Gabbe et al 2016, MacKenzie et al 2008, Nirula and Brasel 2006, but the reasons for this are unknown. It has been suggested that this may, in part, relate to greater clinical expertise, experience and staffing levels within allied health (Gabbe et al 2012), whose interventions are specifically focused on this aspect of patient recovery.…”
Section: Introductionmentioning
confidence: 99%